Alpheus midas sp. nov., a new western Atlantic snapping shrimp from the A. armillatus H. Milne Edwards, 1837 species complex (Decapoda: Alpheidae) - Pachelle, Paulo P. G.; Anker, Arthur (Zootaxa, 2024)
A new snapping shrimp, Alpheus midas sp. nov., is described based on two male specimens caught at a depth of 15–20 m off the coast of Ceará, north-eastern Brazil. The new species belongs to the A. armillatus H. Milne Edwards, 1837 species complex and is most closely related to the western Atlantic A. amarillo Anker, 2012 and A. punctatus Anker, 2012, and the eastern Pacific A. scopulus Kim & Abele, 1988, but can be distinguished from each of them by a suite of subtle morphological and/or colour pattern characters.